Building block for success: A case study of capacity-strengthening in grant administration for Pakistani universities. - Mustafa Hassan; Bakhtawar Ghafoor; Gerald Bloomfield; Ayeesha Kamal; Aysha Almas; Safia Awan; Muhammed Tariq; Salim Virani; Zainab Samad (PLoS ONE)
Background Grant administration plays a pivotal role in the success of research and academic endeavors. However, in Pakistan, academic institutions often face challenges in this domain, primarily due to a lack of specialized training and infrastructure. Aims This research paper presents the outcomes of a comprehensive capacity-strengthening workshop, hosted in two cities, aimed at improving grant administration skills in Pakistani academic institutions. Methodology A pre and post-survey analysis was conducted to assess participants' knowledge and experience. A pre-survey method was used to develop the learning objectives and content for the workshop, whereas the post-survey tool was used to assess the immediate effect of a two-day capacity-strengthening workshop on participants' knowledge of grants. Results Response rates for Karachi participants were 86% pre and 87% post, while for Islamabad participants, they were 63% pre and 57% post. Notably, participants in Islamabad, where infrastructure and support services are often less advanced, exhibited significant improvement in their understanding of grant administration processes. Factors contributing to the workshop's success included its dynamic content, interactive learning methods, and an inclusive learning environment. Conclusion The outcomes of this research provide insights into the effectiveness of tailored capacity-strengthening programs in addressing the unique needs of diverse academic institutions. In addition, it highlights the potential of collaborative learning, where participants from various backgrounds come together to enhance their collective knowledge. This initiative underscores the importance of enhancing grant administration skills to foster a more robust research ecosystem in Pakistan.